2016
DOI: 10.18632/oncotarget.9410
|View full text |Cite
|
Sign up to set email alerts
|

GLK/MAP4K3 overexpression associates with recurrence risk for non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer death worldwide. Non-small cell lung cancer (NSCLC) accounts for 85% of total lung cancers; 40% to 60% of NSCLC patients die of cancer recurrence after cancer resection. Since GLK (also named MAP4K3) induces activation of NF-κB, which contributes to tumor progression, we investigated the role of GLK in NSCLC. GLK protein levels of 190 samples from pulmonary tissue arrays and 58 pulmonary resection samples from stage I to stage III NSCLC patients were studied using imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
(31 reference statements)
2
28
0
Order By: Relevance
“…GLK is a highly desirable drug target for disease areas that include Still's disease (in which patients present with clinical symptoms similar to systemic lupus erythrmatosus), breast cancer, and possibly nonsmall cell lung cancer . We have observed that GLK, like Map4k4, has a glycine right before the Tyrosine in the activation loop and forms an activation loop‐swapped dimer [Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLK is a highly desirable drug target for disease areas that include Still's disease (in which patients present with clinical symptoms similar to systemic lupus erythrmatosus), breast cancer, and possibly nonsmall cell lung cancer . We have observed that GLK, like Map4k4, has a glycine right before the Tyrosine in the activation loop and forms an activation loop‐swapped dimer [Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that GLK effects apoptosis by modulating BH3‐only proteins at the post‐transcriptional level, resulting in activation of the mitochondrial‐dependent intrinsic apoptosis pathway . Recently GLK upregulation has been found to be associated with recurrence of nonsmall cell lung cancer …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLK is activated by stimuli including ultraviolet radiation and several proinflammatory cytokines [84], and has clear roles in the pathogenesis of both autoimmune disease and cancer [85]. Clinically, GLK overexpression predicts poor overall and progression-free survival in non-small-cell lung carcinoma (NSCLC) [86], though the mechanisms through which GLK contributes to disease pathogenesis are not clear at this time. However, emerging evidence suggests that GLK regulates T-cell activation via IL-17A signaling [87].…”
Section: Other Mapk Family Membersmentioning
confidence: 99%
“…Approximately 85% of lung cancers are nonsmall cell lung cancers (NSCLC) [2,3] , and although the number of surgical candidates has increased [1] , only 15-30% of the patients are suitable for surgical resection with a curative intent [2,4] .…”
Section: Introductionmentioning
confidence: 99%